Protocol for the Treatment of Gingival Recession with Platelet-rich Fibrin Membrane - Lázaro Sarduy Bermúdez; Olga Lidia Véliz Concepción; Felisa Veitia Cabarrocas; Manuel Antonio Arce González; Bárbara Toledo Pimentel; Marysol Rodríguez Felipe (Editorial Ciencias Médicas, 2024)
Introduction: It is necessary to apply action protocols as tools to homogenize regenerative periodontal plastic procedures and to establish the guidelines for the periodontist to approach gingival recession with this advanced therapeutic modality. Objective: To design a protocol for the treatment of gingival recession using platelet-rich fibrin membrane associated with coronal advancement flap. Methods: A research with a qualitative approach was carried out in the School of Stomatology of Villa Clara, from July 2020 to December 2021. For the design of the protocol, a preparation phase and an elaboration phase were used; within the latter, three moments were structured: systematic review of the literature, application of group techniques (focal and nominal group) and conclusion of the document. An evaluation by external specialists was carried out before finalizing the definitive structure of the protocol. Results: Five guides for the preparation of protocols, five medical and nursing care protocols and 10 stomatological protocols were consulted. The structure of the document consisted of: cover page, introduction, objectives, target professionals, target population, elaboration process, procedure, algorithm, implementation and revision date, implementation process, evaluation indicators, glossary and bibliographic references. Conclusions: An action protocol was designed that establishes the guidelines for carrying out the regenerative therapeutic procedure, from the selection of patients to the evolution of the therapy. The document was positively evaluated by external specialists.